(untitled) (CIPEEX, 2025)
The Human Immunodeficiency Virus (HIV) remains one of the most relevant pathogens in global public health, particularly affecting vulnerable populations such as older adults. This study reports the experience of an extension project developed by medical students from UniEvangélica at Casa de Acolhimento Bethânia, an institution that houses elderly individuals living with HIV in Anápolis, Goiás. During the first semester of 2024, weekly visits were carried out with recreational, educational, and physical activities, aimed at promoting physical and mental health while also combating the social stigma associated with HIV. The initiative demonstrated the transformative power of health education and humanized care, breaking barriers of prejudice and promoting social inclusion. This project highlights the importance of continuous university extension activities in improving the quality of life of vulnerable and marginalized populations.